Antimicrobial properties of the biosurfactant mannosylerythritol lipids-B against Cutibacterium acnes ATCC 6919 and Listeria monocytogenes CLIST 4165 - Coelho, Ana Letícia Silva (2023)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia de Alimentos, Florianópolis, 2023.